The effect of beam width and crack-depth ratio on mode I fracture toughness of RCB: an experimental and numerical study - Seleem S. E. Ahmad; Ghada M.A. Gamiaa; Abd El-Monem I. El-Kholy (Fracture and Structural Integrity)
In the present work, the fracture performance of pre-cracked reinforced concrete beams was investigated numerically and experimentally. Experimental and numerical programs were designed to examine the effect of beam width, b, (120 and 250 mm) and crack-to-depth ratio, a/d, (0.1, 0.2 and 0.3) for concrete strength, fc, (40 MPa), on the behavior of stress intensity factor, K1C, and fracture energy, G, for reinforced concrete, RC, beams. The work utilized beams with three-point loading conditions experimentally. Through the use of the ANSYS program, a comprehensive 3-D finite element analysis was conducted with utmost precision to simulate and idealize all experimental specimens. It has been confirmed through numerical and experimental outcomes that the stress intensity factor for RC concrete beams experiences a significant increase as the a/d increases. Furthermore, the fracture toughness values in this study show a slight increase due to the utilization of RC concrete beams with wider width. The validity of the presented concept was demonstrated by comparing the experimentally measured load vs. deflection values to the predicted numerical values and finding them to be acceptable